16S rRNA sequences of Exiguobacterium spp. bacteria dominant in a biofloc pond cultured with whiteleg shrimp, Penaeus vannamei. (21st January 2022) - Manan, Hidayah; Rosland, Natasya Ain; Mat Deris, Zulaikha; Che Hashim, Nurul Fakriah; Kasan, Nor Azman; Ikhwanuddin, Mhd; Suloma, Ashraf; Fauzan, Fazlan
Abstract: Biofloc technology is being applied increasingly in shrimp aquaculture. Many countries have adopted this technology to increase shrimp aquaculture production. Owing to its major importance, this study was conducted to identify the bacterial population from biofloc aquaculture shrimp pond water of Singkir Laut, Kedah, Malaysia. Samples of mature biofloc were collected from the biofloc pond water at different shrimp ages (day of culture [DOC]): DOC30, DOC60 and DOC90. Overall, 43 sequences of bacterial species were blasted, which were identified as Exiguobacterium spp., Bacillus spp., Vibrio spp., Acinetobacter junii, Cobetia marina, Rheinheimera aquimaris and Pseudoalteromonas spp. These bacterial species were identified mostly from heterotrophic plate count agar. The bacterial species of Exiguobacterium aestuarii, Exiguobacterium profundum and Exiguobacterium aurantiacum were identified with 16S rRNA gene sequence similarities of 98.45–99.44%. Bacterial species of Bacillus pumilus, Bacillus velezensis, Bacillus cereus, Bacillus safensis and Bacillus subtilis were identified with 16S rRNA gene sequence similarities of 98.81–99.21%. Bacterial species of Vibrio diazotrophicus, Vibrio diabolicus, Vibrio natriegens and Vibrio harveyi were identified with 16S rRNA gene sequence similarities of 98.03–99.19%. Bacteria from Rheinheimera aquimaris were also identified with 16S rRNA gene sequence similarities of 98.69–99.26%; this bacterium is a novel bacterium identified from biofloc samples of the present study and has not been reported from biofloc samples in any previous study. Exiguobacterium spp. from the novel strains of E. aestuarii and E. profundum were identified as dominant, with 23 of 43 samples isolated from a shrimp pond at time points DOC30, DOC60 and DOC90; these bacteria are Gram‐variable rod‐shaped organisms that are capable of producing extracellular enzyme activity to break down chemical structures, thereby helping to remove organic compounds from aquaculture waste. Exiguobacterium spp. are usually identified in tidal flat sediments and on muddy sea coasts. This discovery is consistent with the site of the shrimp pond near to a muddy beach area, which might be the source of seawater leading to the predominance of this type of bacteria in the biofloc samples in the studied pond.